Law Enforcement against the Illegal Fishing of Napoleon Fish (Cheilinus Undulatus): An Empirical Legal Study in Gorontalo Province - Nabila Katili; Lisnawaty W. Badu; Muhamad Khairun Kurniawan Kadir; Anna Boumpa (al-Battar: Jurnal Pamungkas Hukum, 2026)
The illegal fishing of Napoleon fish (Cheilinus undulatus), one of the protected marine species, is still a serious threat to the sustainability of marine ecosystems in Indonesia, including in Gorontalo Province. Although a regulatory framework on fisheries resource conservation is in place, the effectiveness of its enforcement implementation still faces various challenges. This study aims to analyze the legal arrangements regarding the protection of Napoleon fish, evaluate the implementation of law enforcement against illegal fishing practices, and identify the ecological impact caused in the Gorontalo waters. This study uses an empirical legal method with a socio-legal approach. The data was collected through literature studies, in-depth interviews with the Directorate of Water and Air Police (Ditpolairud) of the Gorontalo Police, the Gorontalo Provincial Marine and Fisheries Service, and coastal communities, then analyzed qualitatively. The results of the study show that law enforcement against the illegal fishing of Napoleon fish has not been effective due to limited supervisory resources, weak coordination between agencies, and low legal awareness of coastal communities. In addition, the monitoring and control mechanism for the trade and use of Napoleonic fish is still not able to prevent the practice of illegal fishing optimally. These conditions increase the risk of coral reef ecosystem degradation and threaten the sustainability of fishery resources. This study emphasizes that the effectiveness of Napoleon fish protection requires strengthening the capacity of law enforcement officials, integrating cross-sector supervision, and increasing community participation as the main prerequisites for the realization of sustainable marine conservation governance.